Novel air classification process to sustainable production of manufactured sands for aggregate industry - Petit, Andres (2018)
This work addresses the performance of an own design equipment to classify and clean manufactured sands in a novel sustainable air classification process. The proposed methodology does not use water as the main advantage against the actual wet washing process used in most stone quarries. A real quarry producing 10.4 tons/h of manufactured sands was evaluated and compared with the proposed technology in terms of material balances, types and physical characteristics of products obtained, energy consumptions expressed as CO2 equivalent and local environmental impact. The novel air classification process, tested on a pilot scaled plant, proves to be more efficient than the traditional wet washing process. The main advantage is the production of three aggregates with different particles sizes and without moisture content, against a single wet product obtained by the conventional method.